Chronic Disease Management in a Nurse Practitioner-Led Clinic: An Interpretive Description Study - Natalie Floriancic BScN, MScN, RN; Anna Garnett BScN, MSc, PhD; Lorie Donelle RN, PhD, FCAN (SAGE Open Nursing)
Introduction Nurse practitioner-led clinics (NPLC) represent a model of care that has the potential to enhance primary healthcare delivery to community-dwelling adults who are living with chronic disease by providing greater access and continuity of care and reducing the burden on acute care settings. However, there is limited understanding of nurse practitioners’ experiences and perspectives on supporting adults in chronic disease management within an NPLC model of care. Increased understanding would contribute to our ability to evaluate the effectiveness of the NPLC model of care for chronic disease management. Objective This study explored current chronic disease management practices implemented by nurse practitioners within NPLC throughout the Province of Ontario. Methods A qualitative study was implemented using interpretive description. In-depth interviews were conducted between January 2021 and May 2021 with nurse practitioners who were practicing within NPLCs across Ontario. Data was analyzed using thematic analysis. Results Eleven interviews were completed with nurse practitioners who provided care to community-dwelling adults who were managing chronic disease in a range of geographic settings. Resultant themes included: the nurse practitioner role in bridging access to patients who fall between the cracks, benefits of interprofessional care, meeting a patient where they are at, and addressing healthcare system burden. Conclusion Results suggest that NPLCs are well-positioned to support community-based patients living with chronic disease through provision of on-site interprofessional care, continuity in service provision and increased access to primary healthcare services. This article provides insights into the nurse practitioner led primary healthcare model and how it can facilitate access to services, foster patient self-management and provide a successful alternative model of care.